2021
DOI: 10.1038/s41467-021-21033-6
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule force spectroscopy reveals the dynamic strength of the hair-cell tip-link connection

Abstract: The conversion of auditory and vestibular stimuli into electrical signals is initiated by force transmitted to a mechanotransduction channel through the tip link, a double stranded protein filament held together by two adhesion bonds in the middle. Although thought to form a relatively static structure, the dynamics of the tip-link connection has not been measured. Here, we biophysically characterize the strength of the tip-link connection at single-molecule resolution. We show that a single tip-link bond is m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 102 publications
4
27
0
Order By: Relevance
“…It is also possible that a large number of PCDH15 molecules may be necessary for rebinding to CDH23 in the event of tip link breakage. Atomic force microscopy experiments indicate that the lifetime of the PCDH15-CDH23 bond is only ~8 seconds at resting tension, suggesting that the tip link is a highly dynamic connection (Mulhall et al, 2021). A pool of nearby PCDH15 molecules may enable fast recovery after tip links are broken.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that a large number of PCDH15 molecules may be necessary for rebinding to CDH23 in the event of tip link breakage. Atomic force microscopy experiments indicate that the lifetime of the PCDH15-CDH23 bond is only ~8 seconds at resting tension, suggesting that the tip link is a highly dynamic connection (Mulhall et al, 2021). A pool of nearby PCDH15 molecules may enable fast recovery after tip links are broken.…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of this interaction is such that a mutation in a single residue at the interface can abolish it completely, leading to a high level of conservation at such sites. Together, these results and biophysical experiments (Mulhall et al 2021) revealed that the CDH23-PCDH15 interaction is strong enough to withstand the physiological forces that it would be subjected to in the inner ear. Furthermore, CDH23 and PCDH15 have been identified in zebrafish and chicken hair cells (Söllner et al 2004;Seiler et al 2005;Goodyear et al 2010), suggesting that this interaction and its role in inner-ear mechanotransduction is conserved among vertebrates.…”
Section: Introductionmentioning
confidence: 69%
“…While the CDH23-PCDH15 EC1-2 dimer is ultimately responsible for force transduction, it does so in the context of other structural features that may exhibit functionally significant species-specific changes. The PCDH15 X-dimer, formed at an EC2-3 interface, and an interaction facilitated by MAD12, are two points of dimerization in PCDH15 that have functional implications upon the application of force (De-la-Torre et al 2018;Dionne et al 2018;Ge et al 2018;Choudhary et al 2020;Mulhall et al 2021), and may have evolved to respond to different frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…For each histogram, we construct frequency distribution using the Kernel density smoothing function (in MATLAB). For the Kernel density estimation, we determined the bandwidth using the following equation 46 , 74 76 H: bandwidth, n: number of measurements and σ = min{σ x , IQR/1.34} where σ x : standard deviation and IQR is the interquartile range.…”
Section: Methodsmentioning
confidence: 99%
“…These two proteins as tip-links receive tensile forces of varying magnitudes ranging from 10 to 100 pN from sound-stimuli and convey the force to ion channels during mechanotransduction in hearing. Interestingly, the lifetime of the tip-links complex is measured at varying tensile forces using PAP-based SMFS 46 ; however, the force-responsive behaviour of the constituent cadherins has conveniently been measured using HAP configuration 47 , 48 . Whether the complex configuration of tip-link has any implication on the force-response of constituent cadherins is thus unclear.…”
Section: Introductionmentioning
confidence: 99%